Affective Touch Enhances Self-Face Recognition During Multisensory Integration. Issue 1 (December 2017) - Panagiotopoulou, Elena; Filippetti, Maria; Tsakiris, Manos; Fotopoulou, Aikaterini
Abstract Multisensory integration is a powerful mechanism for constructing body awareness and key for the sense of selfhood. Recent evidence has shown that the specialised C tactile modality that gives rise to feelings of pleasant, affective touch, can enhance the experience of body ownership during multisensory integration. Nevertheless, no study has examined whether affective touch can also modulate psychological identification with our face, the hallmark of our identity. The current study used the enfacement illusion paradigm to investigate the role of affective touch in the modulation of self-face recognition during multisensory integration. In the first experiment (N = 30), healthy participants were stroked on the cheek while they were looking at another face being stroked on the cheek in synchrony or asynchrony with affective (slow; CT-optimal) vs. neutral (fast; CT-suboptimal) touch. In the second experiment (N = 38) spatial incongruence of touch (cheek vs. forehead) was used as a control condition instead of temporal asynchrony. Overall, our data suggest that CT-optimal, affective touch enhances subjective (but not behavioural) self-face recognition during synchronous and spatially congruent integration of different sensations and possibly reduces deafference during asynchronous multisensory integration. We discuss the role of affective touch in shaping the more social aspects of our self.